CARDI in the year 2000 - George, Calixte (CARDI St. AugustineTT, 1991)
Looks at agriculture's contribution to the economy; the human resource factor; hemispheric and regional policy initiatives; constraints to agricultural development; addressing the institutional constraints; tourism; future CARDI research and development perspectives; and, CARDI programmes.